Standard Operating Procedures (SOP) for phenotyping data management in IITA cassava breeding programme - Peteti, P.; Agbona, A.; Ekanem, U.; Toyinbo, S.; Dhikrullah, M.; Adetuyi, M.; Mberu, E.; Rabbi, I.; Kulakow, P. (International Institute of Tropical Agriculture, 2024)
Data management involves data collection, curation, analysis, and storage to ensure accessibility to quality data. The goal of data management is to provide breeders with relevant information and tools that help to take better breeding decisions.